Analysis of The Effect Leverage on Audit Delay with Firm Size as Moderation variable in Banking Sector Companies on The Indonesia Stock Exchange - Yesy (MABIS, 2025)
This study aims to analyze the effect of leverage on audit delay with firm size as a moderating vaiable in 42 companies obtained with criteria IPO before 2018 and have complete financial report data for research . The secondary data source used was financial reports on the Indonesian Stock Exchange. Data analysis was carried out using multiple linear regression techniques and regression moderation analysis. The research results show that leverage have a positive effect on audit delay, while firm size is not able to moderates the relationship between leverage on audit delay. The implications of these findings can be used as a basis for assessing the cause of audit delay practiced carried out by the company.